USING QUIZIZZ GAME TO IMPROVE STUDENT’S VOCABULARY MASTERY IN GRADE VIII C AT MTs IBNU ROSYAD - Nila Komalasari; Mukminatus Zuhriyah (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2021)
The Covid-19 pandemic situation made the government announce the use of e-learning. With this policy, teachers are expected to apply interesting media to be studied. This research aimed to find out whether or not Quizizz Game could improve students’ vocabulary mastery and the supporting and inhibiting factors of the success of Quizizz Game implementation. It was a collaborative Classroom Action Research (CAR). The subject of this research was grade VIII-C of MTs Ibnu Rosyad in the academic year of 2020/2021 which consisted of 20 students. This research was conducted in two cycles which each consists of planning, acting, observing, and reflecting. The data were gathered through qualitative and quantitative data. The results of this research showed that there was improvement from cycle 1 to cycle 2. It can be seen from the mean score of pre-test were 53, the mean score of post-test 1 was 69 and the mean score of post-test 2 was 84. The students' attention and motivation also helped use of Quizizz. But, limited school facilities and wifi become the obstruction